Total Ankle Replacement vs Ankle Arthrodesis (TARVA): A Randomised, Multi-Centre Trial in Patients Over 50 with End Stage Ankle OA, Comparing Clinical and Cost-Effectiveness. Issue 1 (January 2022) - Goldberg, Andrew J.; Molloy, Andrew P.; Davies, Mark Bowen; Hepple, Steve; Thomas, Rhys H.; Siddique, Malik S.; Loveday, David T.; Dhar, Sunil; Bing, Andrew J.; Karski, Michael; Bendall, Stephen P.; Rogers, Mark; et al.
Category: Ankle Arthritis; Ankle; Other Introduction/Purpose: Both ankle replacement and ankle arthrodesis are offered as treatments to patients with end stage ankle osteoarthritis. Systematic reviews have confirmed that both procedures are effective but there has never been a robust randomised multicentre level I study comparing the two treatments. Our objective was to investigate and compare the clinical and cost effectiveness and complication rates of ankle replacement against ankle arthrodesis in the treatment of end-stage ankle osteoarthritis in patients aged 50-85 years. Methods: 17 NHS centres and 35 surgeons across the United Kingdom participated. Formal Ethics committee approvals were obtained. A Trial Management Group was overseen by a Trial Steering Committee, and an Independent Data Monitoring Committee. Randomisation was carried out using a secure on-line service and was stratified by surgeon and the presence or absence of adjacent joint OA (based on an independently reviewed preoperative MRI scan). Participants were randomised 1:1 to either TAR or ankle fusion. The primary outcome was the change in the Manchester Oxford Foot & Ankle Questionnaire (MOXFQ) walking/standing domain scores between pre-operation and 52 weeks post-operation. Secondary outcomes measures included FAAM; FAAM (ADL); and Sport subscale scores. Quality of life was measured using the EQ-5D-5L. Total range of motion was measured using a validated method. Radiological parameters and adverse events were captured. Health economic analysis used mean incremental cost per quality-adjusted life years (QALY) gained. Results: 1600 patients were screened for eligibility. 330 participants were consented and 303 were randomised; 282 underwent surgery and attended follow-up visits. Mean age was 68 years (71% male). The aetiology of OA was post-trauma in 60%, with 6% patients having inflammatory OA. 42% had MRI evidence of OA in the adjacent joints. The groups were well balanced at baseline on all other parameters including deformity, range of motion and baseline clinical and quality of life scores.42% had MRI evidence of OA in the adjacent joints. 54% TARs used were fixed bearing; 46% were mobile bearing. 61% of fusions were performed arthroscopically. We present all outcomes including adverse effects (death; thromboembolic events; reoperation and revision); radiological findings; and range of motion. We also present subgroup analyses looking at the performance of fixed versus mobile bearing implants; differences by age; and by the presence or absence of adjacent joint OA. Conclusion: This is the first publicly funded, multicentre, prospective, randomised clinical trial comparing the clinical and cost effectiveness of ankle replacement against ankle fusion. It is also the first study in surgery to have detailed prospectively captured health economic data to be able to feed into the reimbursement discussions on these life transforming treatments. Due to contractual requirements of the funders the formal results cannot be released until the final report has been submitted for peer review which will not happen until the end of April 2021. The paper is submitted on behalf of the TARVA Study Group.